Fibrous reinforcing system to increase the shear resistance of high strength concrete - Santos, S. P. F. (2008)
The available research has evidenced that discrete steel fibers can increase significantly the shear resistance of High Strength Concrete (HSC) structural elements when High Strength Fiber Reinforced Concrete (HSFRC) is designed in such way that fiber reinforcing mechanisms are optimized. In general, the increase of the concrete compressive strength is associated to an increase of its compactness, resulting benefits in terms of durability, but a strong concern emerges related to the integrity of this material, since it fails in a too brittle mode when submitted to high temperatures. To contribute for the knowledge about the benefits provided by discrete steel fibers when added to HSC applied to laminar structures, an experimental program composed of slab strips submitted to shear loading configuration was carried out. Uniaxial compression tests with cylinders of 150 mm diameter and 300 mm height, and bending tests with 600×150×150 mm3 beams were executed to assess the compression and bending behavior of the developed HSFRC. To evaluate the influence of the percentage of fibers in the shear resistance of laminar structures, three point loading tests with slab strips of 800×170×150 mm3 dimensions were performed. Taking the obtained experimental results, the applicability of the formulation proposed by RILEM TC 162-TDF was evaluated. Test results showed that, even with relative low dosages of steel fibers, the increment in shear resistance was significantly increased. The main obtained results in the research program are presented and discussed in this paper.